2013
DOI: 10.19026/ajfst.5.3108
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Blanching on Properties of Water Yam (<em>Dioscorea alata</em>) Flour

Abstract: Properties of flour from blanched tubers of two water yam (Dioscorea alata) cultivars were compared with those from the non blanched ones. The results showed that the proximate composition of flours from the yellow cultivar was different from that of the purple cultivar. Steam blanching (97±2°C, 7 min) on the purple cultivar resulted in more significant reduction on yield and the Lightness (L) value. However, it had significant effect on some components of the flours such as protein, ash, amylose and fiber. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
55
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(68 citation statements)
references
References 37 publications
7
55
2
3
Order By: Relevance
“…Water yam flour can serve as a source of energy and nutrients (carbohydrates, beta-carotene and minerals) and can provide dietary fiber to processed food products. Addition of various proportions of water yam flour to wheat flour can enhance its nutritive values in terms of fiber and bioactive compounds such as resistant starches, dioscorine, diosgenin and a water soluble polysaccharides [8]. Yams (Dioscorea spp.)…”
Section: Introductionmentioning
confidence: 99%
“…Water yam flour can serve as a source of energy and nutrients (carbohydrates, beta-carotene and minerals) and can provide dietary fiber to processed food products. Addition of various proportions of water yam flour to wheat flour can enhance its nutritive values in terms of fiber and bioactive compounds such as resistant starches, dioscorine, diosgenin and a water soluble polysaccharides [8]. Yams (Dioscorea spp.)…”
Section: Introductionmentioning
confidence: 99%
“…The OAC for these different oils were higer than those obtained from yam Dioscorea. alata cv yellow (0.96 g/g) flour [20] and lower in potato flour (168± 10.95 %) [21] and Nigerian jackfruit seed flour (300 %) [22]. However, the cooking on embers decreased significantly (P <0.05) the absorption capacity of olive oil, maize oil, red oil, dinor oil and sunflower oil from Dioscorea bulbifera flours cv Dougou-won.…”
Section: Resultsmentioning
confidence: 99%
“…As the temperature higher than 50°C, there was a progressive increase in swelling power of yam [20]. In this research, the starch granules gelatinization during steaming about 100°C, starch granule hydrate progressively, hydrogen bonds are ruptured resulting in crystalline regions being converted into amorphous regions and granules continue to imbibe water and swell [16,20], caused starch granules swelled and collapse [16]. It was observed in Table 5 that Da shan line 2 showed the higher swelling power (11.4, 8.5 and 8.6 g/g) than Tainung 5 (8.3, 7.6 and 6.9 g/g), but similar to the results of Heng chun (9.2, 9.1 and 8.1 g/g).…”
Section: Solubility and Swelling Power Evaluation Of Steamed Rice Bowmentioning
confidence: 85%
“…Especially, yam has higher amylose content when comparing to potato, rice and cassava [17]. Previours research further reported the yam with 21.69-31.56% amylose content [16], which amylose retrogrades quickly during the first few hours of cooling after gelatinization during steamed rice bowl cake preparation [5].…”
Section: Resistant Starch Type III Content (Rsc) Of Steamed Rice Bowlmentioning
confidence: 99%
See 1 more Smart Citation